Not getting lost in society: On qualitative analysis - Beuving, Joost; de Vries, Geert (Doing Qualitative Research, 2015)
Having acquainted ourselves in the previous four chapters with different strategies for collecting information about society, we must now discuss what to do with this information. It is important to reiterate from Chapter 1 that in naturalistic inquiry the analysis of information is typically not postponed until the end of a research project. Analysis forms an integral part of the arc of naturalistic inquiry: it is continuous work-in-progress. One observation leads to another one and then to further ones after that. Their succession helps to increase focus. ‘What should I explore next?’ Similarly, one informant may suggest another one. After